Using creative problem solving (CPS) to improve leadership in a non-profit organization - Cardoso de Sousa, Fernando (2016)
The purpose of this study was to evaluate the effectiveness of the Creative Problem Solving (CPS) method in improving the leadership process in a non-profit organization. The research was designed around an intervention and structured in three stages (pre-consult, intervention and follow-up), with a team designated by management, in order to bring leadership cohesion to both departments of the organization and also between the board and executive management. The results, expressed in the tasks performed and in the interviews to team members, allowed us to conclude on the effectiveness of the CPS method to improve organizational leadership, by establishing a stronger relationship between departments, as well as, in the long term, between the board and executive management. These results highlight possible solutions to improve the leadership of non-profit organizations.